KORELASI ANTARA UMUR DENGAN BOBOT KARKAS PADA SAPI PERANAKAN LIMOUSIN DI RUMAH POTONG HEWAN KECAMATAN SUKOREJO KOTA BLITAR - Salnan Irba Novaela Samur (Universitas Islam Balitar, 2022)
The livestock species known as beef cattle produces meat as its main product. Limousin crossbreed cattle are one type of beef cattle that are cultivated in Indonesia. The Limousin Peranakan cattle are the descendants of the local Ongole Peranakan (PO) cattle with the original Limousin cattle. Livestock growth is influenced by various factors, including body weight, carcass age, breed and feed quality. The purpose of this study was to determine whether the carcass weight of Limousin-breed cattle at the Sukorejo District Slaughterhouse, Blitar City, correlated with age. The Sukorejo District Slaughterhouse in Blitar City served as the site of data gathering for this study for two weeks in June 2023. Field studies were used as the method in this study. 30 tails and carcasses of male and female limousines were raw materials in the study. In Microsoft Excel software, correlation analysis is performed using the data that has been collected. The average carcass weight for Limousin-breed cattle is 182.667, and the correlation value is -0.18. Age and carcass weight have a very weak, negative connection that is not considered to be significant. According to research conducted at the Blitar City Slaughterhouse, there is a very low negative correlation between age and carcass weight in Limousin Peranakan Cattle. This is because most of the feed is digested into fat, by older cattle resulting in a decrease in carcass weight. To maintain maximum livestock yields, environmental factors such as feed availability, housing conditions, temperature, livestock health must all be considered. Keywords: Crossbreed, Livestock, Meat, Slaughter